PENINGKATAN KOSAKATA BAHASA JEPANG MELALUI PERMAINAN UNO STACKO (Penelitian Eksperimen pada Siswa Kelas XI SMA Muhammadiyah 1 Pekanbaru) - Virgadi, Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the use of UNO Stacko game in learning Japanese vocabulary in High School Muhammadiyah 1 Pekanbaru. The purpose of the study was to determine the difference between student’s learning outcomes between classes using the UNO Stacko with a class that did not use the UNO Stacko. The object of research is the students of class XI high school Muhammadiyah 1 Pekanbaru of the academic year of 2017/2018 consisting of two classes, namely class XI IPA 3 and class XI IPA 5. This research uses pretest-posttest design, conducted on two classes of experimental class and control classes. the results of study found that the game UNO Stacko can improve student outcomes in learning japanese vocabulary rather than conventional methods. It’s seen from the evaluation value and the difference of pretest and posttest result of the experimental class has increased, that is 80 for the average value in the experimental class and 62,5 in the control classKeywords: Japanese vocabulary , uno stacko